Analysis of determinants of work performance for seafarers based on Fuzzy Electre Model - Erick P. Massami; Malima M. Manyasi (Journal of Shipping and Trade (JST), 2021)
Nowadays, most shipping companies are aware of the importance of analysing seafarers' work performance. Thus, improving seafarers' work performance or finding out the ways by which seafarers' work performance can be enhanced is becoming one of the decisive factors for the success of any shipping company. Any organization aims to have employees who can accomplish corporate goals and objectives using available resources efficiently and effectively. Manpower performance can be enhanced by putting more emphasis on factors that can stimulate employees' motivational level, creativity and job satisfaction. In this study, we use literature review and experts' opinions to identify determinants of workplace performance for seafarers working with Marine Services Company Limited (MSCL), a shipping company owned by the government of Tanzania. The data is collected from a random sample of 30 seafarers working for the MSCL and a Fuzzy Electre Model (FEM) is developed and applied to determine the significance of the factors and sub-factors for the work performance of seafarers. The fuzzy terms are adopted in order to integrate the uncertainty of subjective judgment when evaluating alternatives. The computational results validate the effectiveness of the developed evaluation model. This study is resourceful for the top management of MSCL, as it points out those factors that can directly affect the performance of her seafarers. Seafarers are important assets of any shipping company and thus, this study helps shipping enterprises devise efficient human resource strategies to get maximum benefit from this kind of assets. More importantly, enhanced seafarers' work performance leads to improved company's productivity and higher service quality and therefore make the shipping company competitive in the trading markets.
Keywords: 650; Analysis; Fuzzy Electre model; Seafarers; Shipping companies; Work performance